2020
DOI: 10.20944/preprints202002.0282.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of Physical Activity Related to Food Addiction in Obese and Overweight Healthy Adults: A Systematic Review

Abstract: Obesity is one of the main causes of morbidity and mortality, and food addiction has been considered one of its phenotypes. The study aims to determine the effectiveness of physical activity (PA), exercise, and sedentary behaviour management in attenuating food addiction in obese and overweight healthy adults. A search strategy was undertaken using MEDLINE, CENTRAL, PsycINFO, and CINAHL until April 2019. A total of 295 studies were found from which seven studies, after duplicates were removed, were included. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Indeed, the impact of exercise and physical activity on food intake continues to be a controversial topic. 6 It has been reported in previous studies [7][8][9][10][11] that physical activity is related to improved well-being, enhanced cognitive functioning, and reduced anxiety and depression. It has also been reported that physical activity is related to improved welfare, enhanced cognitive functioning, reduced nervousness and depression.…”
Section: Topic In Clinical Nutrition/january-march 2022mentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, the impact of exercise and physical activity on food intake continues to be a controversial topic. 6 It has been reported in previous studies [7][8][9][10][11] that physical activity is related to improved well-being, enhanced cognitive functioning, and reduced anxiety and depression. It has also been reported that physical activity is related to improved welfare, enhanced cognitive functioning, reduced nervousness and depression.…”
Section: Topic In Clinical Nutrition/january-march 2022mentioning
confidence: 94%
“…Vigorous exercise may lead to a temporal suppression of appetite, known as “exercise-induced anorexia.”5 Ultimately, “liking” and “wanting” values decrease in active people compared with inactive people. Indeed, the impact of exercise and physical activity on food intake continues to be a controversial topic 6. It has been reported in previous studies7–11 that physical activity is related to improved well-being, enhanced cognitive functioning, and reduced anxiety and depression.…”
mentioning
confidence: 99%